2009
DOI: 10.1096/fj.09-130187
|View full text |Cite
|
Sign up to set email alerts
|

Conformational signals in the C‐terminal domain of methionine adenosyltransferase I/III determine its nucleocytoplasmic distribution

Abstract: The methyl donor S-adenosylmethionine is synthesized in mammalian cytosol by three isoenzymes. Methionine adenosyltransferase II is ubiquitously expressed, whereas isoenzymes I (homotetramer) and III (homodimer) are considered the hepatic enzymes. In this work, we identified methionine adenosyltransferase I/III in most rat tissues, both in the cytoplasm and the nucleus. Nuclear localization was the preferred distribution observed in extrahepatic tissues, where the protein colocalizes with nuclear matrix marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
122
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(128 citation statements)
references
References 64 publications
4
122
0
2
Order By: Relevance
“…The authors speculated that presence of nuclear MAT might provide a continuous source of nuclear SAMe, since SAMe is charged and whether or not it can traverse the nuclear membrane is in debate. In support of this, nuclear accumulation of the active MAT1A protein correlated with higher levels of histone H3K27 trimethylation, an epigenetic modification associated with gene repression and DNA methylation (37). Our findings are consistent with this report.…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…The authors speculated that presence of nuclear MAT might provide a continuous source of nuclear SAMe, since SAMe is charged and whether or not it can traverse the nuclear membrane is in debate. In support of this, nuclear accumulation of the active MAT1A protein correlated with higher levels of histone H3K27 trimethylation, an epigenetic modification associated with gene repression and DNA methylation (37). Our findings are consistent with this report.…”
Section: Figuresupporting
confidence: 92%
“…Recently Reytor et al reported finding MATI/III in the nuclei (37). The authors speculated that presence of nuclear MAT might provide a continuous source of nuclear SAMe, since SAMe is charged and whether or not it can traverse the nuclear membrane is in debate.…”
Section: Figurementioning
confidence: 99%
“…SAM is also known as methionine adenosyltransferase (MAT), catalyzes the formation of S-adenosylmethionine by joining methionine and ATP (Horikawa et al 1990), and plays an important role in plant responses to salt, drought, alkali, and flood stresses (Kamal et al 2012;Chen et al 2014). SAM is also a methyl donor, which controls gene expression by DNA methylation (Reytor et al 2009). The mir-2788 miRNA was the only potential regulatory miRNA of SAM and was differentially expressed between LC and NC in this study, which indicated that it may play an important role in hyper-osmoregulation by regulating the expression of SAM.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression levels obtained were very low under all the conditions tested (growth temperature, cell density for induction, etc.). Addition of tags to other MATs, both at the N-or C-terminal ends, was previously shown to decrease the amount of soluble protein obtained [33], and hence the pT7.7-MATX plasmid that contains the MATX ORF without the His-tag was constructed. Growth and induction conditions of E. coli cells transformed with pT7.7-MATX were studied and optimized.…”
Section: Resultsmentioning
confidence: 99%